The Bigfoot files - Eagar, Lindsay (Candlewick Press, 2018)
Miranda's stress level soars when she finds a pile of unpaid bills and foreclosure notices. Her mother, a cryptozoologist and the author of the Bigfoot Files blog, is always off chasing mythical animals and dragging Miranda with her. And Miranda is tired of it. She agrees to go on one more trip, hoping to prove to her mom that Bigfoot isn't real and convince her to get a real job.